Bonded Cement-Based Material Overlays for the Repair, the Lining or the Strengthening of Slabs or Pavements State-of-the-Art Report of the RILEM Technical Committee 193-RLS - Bissonnette, Benoît; Courard, Luc; Fowler, David W.; Granju, Jean-Louis (RILEM State-of-the-Art Reports, 2011)
Among different approaches that can be considered for concrete rehabilitation, bonded overlays are often the most economical alternative. The primary purpose of overlays is to extend the life of the candidate structures, either by restoring the quality and integrity of the surface and/or the re-establishing or improving the load-carrying capacity. Nevertheless, the durability of bonded overlay systems still draws concerns in the technical community because of bond sustainability problems encountered in a number of cases. At this time, there is still no accepted design approach or methodology that can warrant the practitioner a successful outcome of the repair. This State-of-Art report summarizes the findings with respect to all aspects involved in the overlaying process.